Effect of the combined addition of Zn and Pb on partitioning in sediments and their accumulation by the emergent macrophyte Schoenoplectus californicus - Arreghini, Silvana (2017)
Wetlands usually provide a natural mechanism that diminishes the transport of toxic compounds to other compartments of the ecosystem by immobilization and accumulation in belowground tissues and/or soil. This study was conducted to assess the ability of Schoenoplectus californicus growing in natural marsh sediments, with zinc and lead addition, to tolerate and accumulate these metals, taking account of the metal distribution in the sediment fractions. The Zn and Pb were mainly found in available (exchangeable) and potentially available (bound to organic matter) forms, respectively. The absorption of Zn and Pb by plants increased in sediments with added metals. Both metals were largely retained in roots (translocation factor < 1). Lead rhizome concentrations only increased significantly in treatments with high doses of metal independently of added Zn. The addition of Zn increased its concentration in roots and shoots significantly, while its concentration in rhizomes only increased when both metals were added together. Zinc concentration in shoots did not reach the toxic level for plants. Zinc and Pb concentrations in roots were high, but they were not sufficient to reduce biomass growth.